Clinical study of IUGR cases and correlation of Doppler parameters with perinatal outcome - Sharma, Deepti D.; Chandnani, Kavita C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Early detection and timely intervention in IUGR babies can significantly improve perinatal outcome. Bio physical profile and non stress test have been the common modalities used for foetal surveillance but neither of these is accurate in predicting poor perinatal outcome. With the advent of Doppler, it has become much easier to pick up IUGR cases early and with high reproducibility and efficacy for perinatal outcome. Objectives of this study were 1) to correlate clinical findings in IUGR with colour Doppler and perinatal outcome 2) to study prognostic efficacy of Doppler parameters in early detection of foetal compromise. Methods: Sixty singleton pregnancies diagnosed to have IUGR beyond 30 weeks gestation were included in the study and were examined and followed clinically as well as with Doppler findings till delivery. Prognostic efficacy (sensitivity, specificity, positive and negative predictive values) of umbilical artery and middle cerebral artery waveforms were studied using percentage. Results: The sensitivity and specificity of MCA PI (78%, 93%) as an indicator for extent of foetal compromise in IUGR was highest, though ratios such as MCA PI/UA PI as well as UA SD (>3) were comparably specific predictors for poor perinatal outcome. Absent and reverse end diastolic flow in umbilical artery is associated with definite poor perinatal outcome in terms of mortality. Clinical examination as well as ultrasound biometry has limited accuracy in determining appropriate time of intervention in growth restricted foetuses. Non reactive non stress test was shown to have positive predictive value of only 24% with false positive rate of 75%. Conclusions: Colour Doppler study is a simple, quick, non invasive procedure and multiple vessel study has high accuracy among the other tests for ante partum foetal surveillance.